TEMIR YO‘L TRANSPORTI TARMOG‘INING INNOVATSION RIVOJLANISHIDA INVESTITSIYA SAMARADORLIGINI BAHOLASH METODIKASINI TAKOMILLASHTIRISH (Marketing Journal, 2026)
This study improved the methodology for evaluating investment efficiency in the context of innovative railway transport development. An integrated approach combining financial performance, technical productivity, innovation maturity, and sustainability indicators was developed. The economic outcomes of railway infrastructure modernization, electrification, and digitalization projects were analyzed. The findings provided practical recommendations for supporting investment decisionmaking, improving resource utilization, and strengthening the competitiveness of the railway sector. The proposed methodology contributes to more comprehensive assessment of infrastructure projects and long-term transport development.